Periodontal disease among non-diabetic Coronary Heart Disease patients. A case-control study - Patel, Jenisha; Kulkarni, Suhas; Doshi, Dolar; Poddar, Pawan; Srilatha, Adepu; Reddy, Kommuri Sahithi (Acta Biomedica Atenei Parmensis, 2021)
Summary. Background: There is well documented scientific evidence supporting the association between Coronary Heart Disease (CHD) and periodontitis. It is however, uncertain if this association is causal or is mediated by the common inflammatory pathways. Hence, the study assessed and compared the Periodontal Health Status among CHD patients with age and gender matched controls. Methods: A total of 808 medically confirmed CHD patients were compared with 808 age and gender matched controls. Oral examination was conducted using Simplified Oral Hygiene Index (OHI-S) and modified World Health Organization (WHO) Oral Health Assessment form, 1997. Mean scores were compared using Mann- Whitney-U test and Analysis of Variance (ANOVA). Logistic regression analysed the association between the risk factors and CHD. Results: Cases had significantly higher mean sextants with pockets and attachment loss ≥4mm compared to controls (p≤0.05). The cases also had significantly poor oral hygiene mean scores compared to controls (p=0.0001*). There was a lower and insignificant association between age (p=0.99), gender (p=0.84) and CHD. Risk factors education (p=0.001), lesser frequency of dental visit (p=0.001) also showed a lower, yet significant association. Risk of CHD was higher among tobacco (Odds ratio (OR) - 2.26) and alcohol (OR-1.83) users. Presence of poor oral hygiene (OR-5.20), pocket of ≥6 mm (6.70) and attachment loss of ≥9 mm (OR-11.31) also showed higher risk of CHD. Conclusion: The study results support the association between periodontal disease and CHD. To halt the epidemic of CHD, emphasis on screening of wide age range, reinforcement of public health systems and early detection is recommended. (www.actabiomedica.it)